SKRINING KESEHATAN DAN TUMBUH KEMBANG ANAK USIA PRASEKOLAH DI LA PRESCHOOL JAKARTA PUSAT - Pambudi, Wiyarni; Kurniawati, Bernice Helsa; Yuliavita, Shelvy (Jurnal Bakti Masyarakat Indonesia, 2024)
Golden age is considered as essential period in a child’s growth and development, especially the first three years of life. Stunting which remains as the main indicator of growth in children, where based on Basic Health Research (RISKESDAS) in 2018, 30,8% toddlers in Indonesia had stunting. While indicator of successful toddler development can be seen in toddler’s mental, emotional, social, and independence behavior according to their age. Stimulation, Detection, Early Intervention for Growth and Development Disorders (SDIDTK) as a screening of children's growth and development, needs to be carried out to tell children’s status more objectively. SDIDTK activity was given to 13 (92,9%) children in LA Preschool, involving pediatricians and clerkship students to carry out anthropometric measurement, head to toe physical examination, accompanied by one-on-one interactions to fulfil children’s growth and development examination, with the help of parents to fill g-form questions consists of Developmental Pre-Screening Questionnaire (KPSP) and Emotional Behavior Problem Questionnaire (KMPE) previously. Result of assessment showed children’s growth and development status, followed by stimulating activities for each parent. From the growth screening was found 8 (61,5%) children had good nutritional status, although there were several students with wasting, overweight, underweight, and short stature. In development screening, it was found that all children had normal KPSP and KMPE. Clean and healthy living behavior such as feeding rules, dental and oral health care, prevention of Influenza Like Illness-Severe Acute Respiratory Infections (ILI-SARI), sleep patterns were almost fully applied in LA Preschool students ABSTRAK Golden age dianggap sebagai periode penting dalam tumbuh kembang anak, terutama dalam tiga tahun kehidupan. Hingga saat ini stunting masih menjadi tolak ukur pencapaian pertumbuhan balita, dimana berdasarkan Riset Kesehatan Dasar (RISKESDAS) tahun 2018 sebesar 30,8% balita Indonesia mengalami stunting. Sementara indikator keberhasilan perkembangan balita dilihat dari aspek mental, emosional, sosial, dan kemandirian balita secara optimal sesuai usianya. Kegiatan Stimulasi, Deteksi dan Intervensi Dini Penyimpangan Tumbuh Kembang (SDIDTK) yang merupakan skrining tumbuh kembang anak perlu dikerjakan sebagai salah satu upaya menyampaikan kondisi anak secara lebih objektif. Pelayanan SDIDTK diberikan kepada 13 (92,9%) anak LA Preschool yang melibatkan kerjasama dari praktisi kesehatan anak dan mahaanak kepaniteraan Program Studi Profesi Dokter untuk melakukan pengukuran antropometri, pemeriksaan fisik dari kepala hingga kaki, disertai interaksi untuk melengkapi data tumbuh kembang anak, yang sebelumnya sudah diisi oleh orang tua dalam g-form yang berisikan pertanyaan Kuesioner Pra Skrining Perkembangan (KPSP) dan Kuesioner Masalah Perilaku Emosional (KMPE). Hasil asesmen memaparkan status tumbuh kembang anak, disertai dengan kegiatan stimulasi yang perlu diupayakan oleh masing-masing orang tua. Dari skrining pertumbuhan didapatkan 8 (61,5%) anak berstatus gizi baik, walau masih ditemui anak dengan gizi kurang, gizi lebih, underweight, serta perawakan pendek. Pada skrining perkembangan didapatkan 100% anak memiliki hasil KPSP sesuai usia dan KMPE normal. Kebiasaan perilaku hidup bersih dan sehat meliputi aturan makan (feeding rules), perawatan kesehatan gigi dan mulut, pencegahan Influenza Like Illness-Severe Acute Respiratory Infections (ILI-SARI), dan pola tidur secara keseluruhan sudah dapat diterapkan dengan baik oleh anak LA Preschool.